RAMEPs: A goal-ontology approach to analyse the requirement for data warehouse systems - Ta'a, Azman; Abdullah, Mohd Syazwan; Md. Norwawi, Norita (World Scientific and Engineering Academy and Society (WSEAS), 2010)
The data warehouse (DW) systems design involves several tasks such as defining the DW schemas and the ETL processes specifications, and these have been extensively studied and practiced for many years.However, the problems in heterogeneous data integration are still far from being resolved due to the complexity of ETL processes and the fundamental problems of data conflicts in information sharing environments. Current approaches that are based on existing software requirement methods still have limitations on translating the business semantics for DW requirements toward the ETL processes specifications. This paper proposes the Requirement Analysis Method for ETL processes (RAMEPs) that utilize ontology with the goal-driven approach in analysing the requirements of ETL processes. A case study of student affair domain is used to illustrate how the method can be implemented.